Aktivitas Makan Orangutan Kalimantan (Pongo pygmaeus wurmbii) di Taman Nasional Tanjung Puting Wilayah Camp Leakey Kab. Kotawaringin Barat Sebagai Penunjang Materi Konservasi - Moniktia Yosika Yantoko; Siti Sunariyati; Yohanes Edy Gunawan (Agrienvi: Jurnal Ilmu Pertanian, 2022)
Conservation activities for the Bornean orangutan (Pongo pygmaeus wurmbii) are strongly influenced by several factors in environmental and habitat conditions so that the sustainability of the orangutan population is maintained, including playing an important role in terms of feeding activities and the ability to adapt to eating orangutans in reintroduction areas through monitoring activities in the daily lives of orangutans, emphasizing knowledge of eating activities in the Leakey camp area as an orangutan release conservation institution needs to be done. Observation of the eating activity of orangutans was carried out using the Focal Animal Sampling method. All activities carried out by individuals are observed and recorded. Observations were made starting from leaving the nest at around 06.30 WIB and finished observing at 17.30 WIB. Observations include diet (length of time), type of feed, portion of feed consumed. The data obtained will be tabulated and the percentage determined by displaying the data in the form of tables and charts. The length of time for eating activities of the Gara orangutans occupies the second highest percentage for eating activities, namely 33.0%, resting activity is 55.2% as the most activity and making nests 11.8%, Casper orangutans have the highest feeding activity, which is 91.4% and the second highest play activity 4.6% and the third to make a nest 4.1%. The types of feed consumed by Gara orangutans were 8 species consisting of Gluta renghas L 9%, Mangifera odorata 18%, Pandanus helicopus 14%, Symlecos celastrifolia 4%, Osbornia octodonta 4%, Musa acuminate 23%, Coptotermes curvignathus 14%, Coptotermes sp5% and Casper orangutan 4 species consisting of Diaphania indica s 46%, Mangifera odorata 23%, Musa acuminate 27%, Pimenta officinalis 4%. The portion of feed consumed by the orangutans Gara and Casper is dominated by the fruit portion.